Presidential Decree-Law No. 119 of the Year 2014 Concerning the Suez Canal Investment and Development Certificates = قرار رئيس جمهورية مصر العربية بالقانون رقم 119 لسنة 2014 فى شأن شهادات استثمار وتنمية قناة السويس - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.